2016
DOI: 10.1530/jme-16-0118
|View full text |Cite
|
Sign up to set email alerts
|

T3 enhances Ang2 in rat aorta in myocardial I/R: comparison with left ventricle

Abstract: Angiogenesis is important for recovery after tissue damage in myocardial ischemia/reperfusion, and tri-iodothyronine (T3) has documented effects on angiogenesis. The angiopoietins 1/2 and tyrosine kinase receptor represent an essential system in angiogenesis controlling endothelial cell survival and vascular maturation. Recently, in a 3-day ischemia/reperfusion rat model, the infusion of a low dose of T3improved the post-ischemic recovery of cardiac function.Adopting this model, our study aimed to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…More specifically, nitric oxide (NO) production by VSMC, other than by endothelium, has been considered the driving factor in local regulation of vascular response ( Lee et al, 2008 ) mainly via PI3K/Akt signaling pathway activation ( Carrillo-Sepúlveda et al, 2010 ). Furthermore, it has been observed that both T4 and T3 administration induce new blood vessel formation via surface receptor ανβ3-mediated pathway in human microvascular endothelial cells ( Balzan et al, 2013 ; Liu et al, 2014 ) and in rat heart and aorta tissues during ischemic reperfusion procedure ( Sabatino et al, 2016 ).…”
Section: Ths and CV Systemmentioning
confidence: 99%
“…More specifically, nitric oxide (NO) production by VSMC, other than by endothelium, has been considered the driving factor in local regulation of vascular response ( Lee et al, 2008 ) mainly via PI3K/Akt signaling pathway activation ( Carrillo-Sepúlveda et al, 2010 ). Furthermore, it has been observed that both T4 and T3 administration induce new blood vessel formation via surface receptor ανβ3-mediated pathway in human microvascular endothelial cells ( Balzan et al, 2013 ; Liu et al, 2014 ) and in rat heart and aorta tissues during ischemic reperfusion procedure ( Sabatino et al, 2016 ).…”
Section: Ths and CV Systemmentioning
confidence: 99%
“…Evidence indicates that Dyn-A 1-17 administration causes an increase in total free fatty acids and nor-BNI reduces Dyn-A 1-17 -induced motor dysfunction [63]. Importantly, recent studies suggest that IGF-1 is cardioprotective by inhibiting Na + /H + exchanger activity via phosphorylation at Ser648 of the exchanger [64] and T3 aids in early-phase CV angiogenic sprouting after ischemia/reperfusion (I/R) through angiopoietin-1 and VEGF upregulation [65]; (Fig. 2A).…”
Section: Other Biological Processesmentioning
confidence: 99%